Oxidation of stepped Pt(111) studied by x-ray photoelectron spectroscopy and density functional theory - Bandlow, Jochen; Kaghazchi, Payam; Jacob, Timo; Papp, Christian; Tränkenschuh, Barbara; Streber, Regine; Lorenz, Michael Peter Andreas; Fuhrmann, Thomas; Denecke, R.; Steinrück, Hans-Peter (Physical Review B, 2011)
In this comparative density functional theory and x-ray photoelectron spectroscopy study on the interaction of oxygen with stepped Pt(111) surfaces, we show that both the initial adsorption and oxidation occur at the steps rather than terraces. An equivalent behavior was observed for the oxide formation at higher chemical potentials, where, after the formation of a one-dimensional PtO-type oxide at the steps, similar oxide chains form on the (111) terraces, indicating the initial stages of bulk oxide formation. © 2011 American Physical Society.